PENERAPAN MODEL PEMBELAJARAN BERDIFERENSIASI UNTUK MEMPERBAIKI PROSES PEMBELAJARAN ARITMATIK BARISAN DAN DERET - Cahyati, Nur; Sianipar, Anton Zulkarnain; Novianti, Idha (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
This research aims to improve student's learning activities and outcomes through theapplication of the Differentiated Learning Model using the based Learning method and throughdiscussion. The research will be carried out in two cycles and involves 18 students of class X TKJat SMK Putra Bangsa 01 Cibening. The data used in this study were obtained from the observationof teachers and students as sources of information, which included quantitative and qualitativedata. To see teacher activities and student activities, researchers observed and recorded them onobservation sheets. In addition, data regarding student learning progress was obtained throughwritten tests, such as evaluation of learner work (LKPD) and final evaluation (individualassignment). The results showed that differentiated learning has a positive impact on improvingstudent learning outcomes. It can be seen from the evaluation conducted there was an increase inthe average evaluation score from 77.8 to 84.5. In addition, the percentage of students whoreached the minimum completeness standard (KKM) also increased significantly, from 55% to83%. Therefore, it is recommended for teachers to gradually and continuously review appropriatelearning patterns and strategies to improve learning processes and outcomes.